2005
DOI: 10.1016/j.physc.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of point Josephson junctions in a microstrip line

Abstract: We model the dynamics of point Josephson junctions in a 1D microstrip line using a wave equation with delta distributed sine nonlinearities. The model is suitable for both low Tc and high Tc systems (0 and π junctions). For a single junction in the line, we found two limiting behaviors: the ohmic mode where the junction acts as a pure resistor which stops waves and separates the cavity and the junction mode where the wave is homogeneous throughout the strip. This classification allows to bound the IV curves of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…From remark (8), φ is a polynomial by parts. We define P i+1 (x) the second degree polynomial such that P i+1 (x) = φ(x) for a i ≤ x ≤ a i+1 .…”
Section: Piece-wise Polynomialmentioning
confidence: 96%
“…From remark (8), φ is a polynomial by parts. We define P i+1 (x) the second degree polynomial such that P i+1 (x) = φ(x) for a i ≤ x ≤ a i+1 .…”
Section: Piece-wise Polynomialmentioning
confidence: 96%
“…The electrodes forming the array of junctions are part of the central conductor of a coplanar waveguide allowing radiation detection. The junctions were windowlike fabricated using the standard Nb-AlO x -Nb trilayer technology [18,19] and had a current density of 110 A=cm 2 . The measurements herein presented are part of an investigation performed on arrays which were made of 50, 30, and 25 junctions in parallel; all the measurements were performed at 4.2 K. In Fig.…”
mentioning
confidence: 99%
“…For arrays of equidistant junctions, a recent study by Pfeiffer et al [13] analyzed the fine features of the first resonant step in terms of Cerenkov radiation between a sine-Gordon discrete kink (fluxon) and a cavity mode. For one junction placed arbitrarily in the strip, our theoretical study [14] revealed that all the linear modes are excited with different amplitudes. In particular the junction can stop waves across the strip or enhance them throughout.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%
“…We choose a device with l = p, a 1 = l/3, d 1 = 1 and take three limiting cases j = 0 j = 1 and j = 30. When there is no capacity miss-match (j = 0) we showed in [14] that the resonances of the I-V curve are positioned at V = kp/l with k integer and are bounded by Table 2 together with the coupling coefficient / n (a 1 ). The eigenvalues are clearly not harmonic.…”
Section: Eigenvalues and I-v Curvesmentioning
confidence: 95%
See 1 more Smart Citation